2006
DOI: 10.1017/s0031182006001569
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and characterization of piroplasms infecting cervids and chamois in Northern Spain

Abstract: Wildlife can act as reservoir of different tick-borne pathogens of veterinary and zoonotic importance. To investigate the role of wild ruminants as reservoir of piroplasm infection, 28 red deer, 69 roe deer and 38 chamois from Northern Spain were examined by reverse line blot (RLB) hybridization. The survey detected a prevalence of 85.7% in red deer, 62.3% in roe deer and 28.9% in chamois. Four different piroplasms were identified: Theileria sp. OT3 (previously described in sheep) as the most prevalent (85.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
65
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 33 publications
7
65
4
Order By: Relevance
“…Cervids have previously been reported carriers of theilerids in the Iberian Peninsula (Hofle et al 2004, García-Sanmartín et al 2007. However, the present study is the first to describe the occurrence of T. annulata in deer.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Cervids have previously been reported carriers of theilerids in the Iberian Peninsula (Hofle et al 2004, García-Sanmartín et al 2007. However, the present study is the first to describe the occurrence of T. annulata in deer.…”
mentioning
confidence: 53%
“…Theileria sp. (3185/02) from Spanish red deer has been reported from northern Spain (Hofle et al 2004, García-Sanmartín et al 2007), but a different Theileria sp. (CNY3A), identical to that found in Cervus nippon in Japan (Inokuma et al 2004), was diagnosed by molecular methods in the present survey.…”
mentioning
confidence: 99%
“…Sequencing of the ssu rDNA fragments showed the highest similarity with B. capreoli and B. divergens. Currently, morphological, serological and molecular data do not allow to differentiate between these two species (Garcia-Sanmartin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current species designations have not been supported by recent molecular studies. On the one hand, species have been shown to be molecularly identical, and therefore it has been suggested that they should be considered the same taxon parasitizing different hosts (13). On the other hand, the different strains currently classified as Babesia divergens have been shown to probably belong to more than one species (16).…”
mentioning
confidence: 99%